Nitrogen response and agronomic use efficiency of N fertilizer in diverse commercial maize hybrids at Bako, Western Ethiopia - Begizew Golla (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Agronomic Efficiency indicated the grain yield production potential of variety in response to the applied nutrients. Field experiment was conducted at the research Farm of Bako National Maze Research Center Western Ethiopia during 2020/2021 in order to investigate the nitrogen response and agronomic efficiency of various maize genotypes.  Ten maize varieties were tested under two level of nitrogen (N1 = 0 kg/ha and N2 = 184 kg/ha) in factorial arrangement with three replications. Each variety was planted in uniform spacing of 75x30 cm.  Then response of  each variety for the applied nitrogen were evaluated. Agronomic efficiency of Nitrogen Fertilizer associated with grain yield of various commercial maize varieties was calculated using average grain yield and applied nitrogen to indentify the agronomic efficiency of each maize varieties. Based on calculation result maize hybrid BH661 showed the highest agronomic efficiency (35.42), where as Gibe3 showed the lowest value (4.68) compared to others tested varieties. This result indicated that Gibe3 respond poorly for the applied nitrogen where as Hybrid BH 661 highly responded for the increasing applied N input. The result has indicated the need of specific recommendation for nutrient scarce area, that lack nitrogen or for farmers who lacks money to buy nitrogen fertilizer should be used Gibe3 to get better yield. On other hand in optimum or high nitrogen available condition the hybrids which have high agronomic efficiency should be sown to boost maize grain yield but with taking into account the optimum rain fall and agro ecology of each variety.